ANALISIS KECEPATAN KENDARAAN DAN KINERJA RUAS JALAN RAYA KAPAL AKIBAT AKTIVITAS RUMAH SAKIT MANGUSADA KAPAL, MENGWI, BADUNG - I KETUT SUDIPTA GIRI; I GUSTI AGUNG GDE SURYADARMAWAN; NI KETUT SRI ASTATI SUKAWATI (Universitas Mahasaraswati K. Mataram, 2023)
Mangusada Hospital is one of the hospitals in Badung Regency, which is located in Kapal Village. Hospital activities during operating hours will directly affect the smoothness of traffic on the roads around the hospital caused by the activity of entering and leaving vehicles to or from the hospital. To find out the performance of the Ship Highway section, a research was conducted in the area for three days, namely Monday and Friday representing working days, Sunday representing holidays. Analysis of road performance using the 1997 MKJI calculation procedure for urban road sections. Based on the results of data analysis it is known that the highest vehicle traffic volume on Monday was 3046.05 pcu/hour occurred at 07.15 WITA -08.15 WITA, on Friday it was 2802 pcu/hour occurred at 07.00 WITA - 08.00 WITA, Sunday at 2372.9 pcu/hour occurred at 16.45 WITA - 17.45 WITA. The level of road service during Monday's peak hour was at level C with a degree of saturation value of 0.59, the average speed of light vehicles reached 39 km/hour. The condition of the vehicles at the road service level illustrates that traffic flow conditions are still stable, travel speed and freedom of movement are affected by the large volume of traffic so that the driver can no longer choose the desired speed